2020
DOI: 10.1016/j.redox.2019.101321
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol induces antioxidant pathways in keratinocytes by targeting BACH1

Abstract: Cannabidiol (CBD) is a major non-psychotropic phytocannabinoid that attracted a great attention for its therapeutic potential against different pathologies including skin diseases. However, although the efficacy in preclinical models and the clinical benefits of CBD in humans have been extensively demonstrated, the molecular mechanism(s) and targets responsible for these effects are as yet unknown. Herein we characterized at the molecular level the effects of CBD on primary human keratinocytes using a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
120
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 57 publications
(64 reference statements)
14
120
1
Order By: Relevance
“…The effect of CBD on keratinocytes was examined as follows: all cell groups (control cells, keratinocytes following UVA irradiation, and cells following UVB irradiation) were cultured for 24 h in a medium suplemented with 4 µM CBD (dissolved in ethanol with a final concentration of 0.1%). This concentration of CBD did not alter the morphology or proliferation of keratinocytes [29,30], nor did it affect the cells' viability measured by an MTT assay [28] (data not shown). The control cells were cultured in parallel without treatment.…”
Section: Cell Culture and Treatmentmentioning
confidence: 89%
“…The effect of CBD on keratinocytes was examined as follows: all cell groups (control cells, keratinocytes following UVA irradiation, and cells following UVB irradiation) were cultured for 24 h in a medium suplemented with 4 µM CBD (dissolved in ethanol with a final concentration of 0.1%). This concentration of CBD did not alter the morphology or proliferation of keratinocytes [29,30], nor did it affect the cells' viability measured by an MTT assay [28] (data not shown). The control cells were cultured in parallel without treatment.…”
Section: Cell Culture and Treatmentmentioning
confidence: 89%
“…Furthermore, the exact, obviously cell type-dependent mechanism of HO-1 induction by CBD poses a challenge for future investigations. In this context, a recently published study showed that CBD mediates HO-1 expression in keratinocytes Nrf2 independently by inducing the cytosolic proteasomal degradation of the transcriptional repressor BTB and CNC homology 1 (BACH1) and its nuclear export [43]. Accordingly, no inhibition of the CBD-induced HO-1 expression in the presence of Nrf2 siRNA could be registered in the respective work [43].…”
Section: Autophagymentioning
confidence: 99%
“…CBD is a phytocannabinoid present in the resin secreted from trichomes in female C. sativa plants, and is mainly found in inflorescences. The bioactivity of this compound has been related to an enhancement of its antioxidant and neurological activity, among others, by the promotion of several metabolic pathways [4][5][6]. However, the European Union (EU) does not consider CBD supplements as a novel food [7] and lets member states set their own rules over its marketing, leading to a convoluted situation in terms of regulation.…”
Section: Introductionmentioning
confidence: 99%